Eptinezumab for the treatment of migraine. (3rd August 2021) - Spuntarelli, Valerio; Negro, Andrea; Luciani, Michelangelo; Bentivegna, Enrico; Martelletti, Paolo
ABSTRACT: Introduction: Migraine is one of the most common illnesses in the world, with severe economical and subjective implications. Nowadays specific and nonspecific drugs are used for migraine chronic therapy, but a portion of patients have no benefit from these administrations. CGRP receptor antagonists are a good preventive treatment for episodic and chronic migraine. Areas covered: This article reviews both preclinical and clinical studies on eptinezumab as a potential preventive therapy for migraine, as well as pharmacokinetic and pharmacodynamic features. Thus, it summarizes safety and tolerability data based on human studies. Expert opinion: Eptinezumab had good results in several trials, making this molecule a promising migraine preventive drug. Although preclinical and clinical studies showed a significant efficacy, there are no data on the use of Eptinezumab during pregnancy or breastfeeding. There are still some knowledge limits about its pharmacokinetics and metabolism. This is a matter of concern that should be addressed in future studies.